جماليات المديح النبوي المعاصر بين التقرير والتخييل مجموعة التحبيرة في حدائق السيرة لسعد مردف الجزائري نموذجا - حنانشة علي; حمودة حسن (جامعة الوادي University of eloued, 2025)
أسرت فضائل النبي الشعراء على مر العصور، فاستحوذت على عواطفهم ومشاعرهم. لذا، تستكشف دراستنا جماليات المديح النبوي المعاصر بين الشعر السردي والخيالي، متخذةً ديوان "التحبيرة في حدائق السيرة" لسعد مردف نموذجًا. تتضمن دراستنا لهذا الموضوع مقدمة نظرية وفصلين. في المقدمة النظرية، نناقش السياق الثقافي للمؤلف، مقدمةً بحياته وأعماله. ثم نقدم فصلين، أحدهما نظري، نعرض فيهما مفاهيم أساسية كالمديح النبوي، وتعريفًا بالشعر السردي والخيالي، وأهم تجلياتهما في الخطاب الأدبي عمومًا. أما الفصل التطبيقي، فنستكشف هاتين التقنيتين في ديوان "التحبيرة في حدائق السيرة"، متعمقين في دلالة العنوان كعنصر مهم من عناصر الديوان. ثم نختتم بخاتمة تتضمن أهم النتائج، ثم نورد المراجع. The Prophet's virtues have captivated poets throughout the ages, capturing their emotions and feelings. Therefore, our study explores the aesthetics of contemporary prophetic praise between narrative and imaginative poetry, using the collection "Al-Tahbirah fi Hada'iq al-Sirah" (The Ink in the Gardens of the Biography) by Saad Mardif as a model. Our study of this topic includes a theoretical introduction and two chapters. In the theoretical introduction, we discuss the cultural context of the author, introducing his life and works. We then present two chapters, one of which is theoretical, in which we present basic concepts such as prophetic praise, and a definition of narrative and imaginative poetry, along with their most important manifestations in literary discourse in general. In the applied chapter, we explore these two techniques in the collection "Al-Tahbirah fi Hada'iq al-Sirah," delving into the significance of the title as an important aspect of the collection. We then conclude with a conclusion, including the most important findings, and then provide references.
مذكرة .ماستر . أدب حديث ومعاصر. 2025
Keywords: جماليات المديح النبوي، الشعر السردي، الشعر الخيالي; Aesthetics of Prophetic Praise; Narrative Poetry; Imaginative Poetry